MITIGATING FRAUDULENT RISKS: COMPANY CAPTAINS' PERSPECTIVE - Gunawan, Lenny (Universitas Brawijaya, Indonesia, 2019)
Complete document sets and availability ability tocapture business flow have been underestimated among small-medium business practitioners, affecting the bigger chance of unnecessary loss and increasing risks which prone to fraudulent acts both originally from internal and external parties. This research is equipped with interview transcript involving Mr. Daniel Ifianto, CEO (Chief Executive Operational) of CV. Mandiri Jaya Agro-business (MJA), and his wife as CFO (Chief FinancialOfficer, which main business activity is exporting paddy and corn seeds as respondents.). Second Entity, as the research object, is a CV. DCK which is an architecture and interior design company, Mr. DK.Research Method used is a qualitative study which isinvestigating monetary and operational fraud, errors, and omissionsoccurred both intentional and unintentionally related to the availability of complete documents and Standard Operating Procedure(SOP) application. The research finding shows that solutions were found through creating sets of document copies, authorizations, and document cycle movements concluding parties and people involved both internally and externally. The implication was fraud has been significantly reduced, and the owner feels that applying a complete set of documents andproper authorization has been useful for monitoring the organization itself before fraud happens.